A Brief Analysis on The Mannerism of Strange Stories of A Chinese Studio by Pu Songling - Khosasih, Andyni (Bina Nusantara University, 2012)
Strange Stories of a Chinese Studio, commonly known as 聊斋 (Liaozhai) is a short novel written in classical Chinese from Qing dynasty. This novel was written in 1680, year 19 of Emperor Kangxi’s reign. The novel has 491 chapters. Article explored Pu Songling’s mannerism, such as the contents, material collection, innovation of artistic literary elements and images of women. It can be concluded that the novel reflects the broadness of humanistic world and thoroughly describes images of women. It broke through the restriction of thoughts in feudalism society.